The Urgency of Language as a Tool for Scientific Thinking in Schools: An Approach to Communication Law - Fauzia, Ana; Octavia, Deva Gama Rizky; Hamdani, Fathul (International Journal of Social Learning (IJSL), 2023)
Language as a means of scientific thinking places itself reasonably centrally. Even according to Francis Bacon, human language can gain knowledge and power. In short, language helps both scientists and society to think scientifically. This research uses a communication law approach to analyze the urgency of language as a tool of scientific thinking in schools. The research method used is descriptive research. The research results present a concept of language that acts as a medium for thought processes and that schools are the best environments for cultivating language as a tool for scientific thinking. Because language and thinking are inextricably linked. As a result, in this scenario, language growth in the function of thinking is also meant to enhance science education. As a result, the presence of language as something unique to humans is more than just a sign; it is also a medium for growing the human intellect, particularly in communicating the truth of things. Teachers play a crucial role in the growth and refinement of language as a tool for scientific thinking in schools because they must comprehend the five principles of successful communication: respect, empathy, audibility, clarity, and humility.